Altering Male-Dominant Representations: A Study on Nominalized Adjectives and Participles in First and Second Language German. (December 2016) - Sato, Sayaka; Gabriel, Ute; Gygax, Pascal M.
The generic use of masculine plural forms in grammatical gender languages has been criticized for activating unequal gender representations that are male dominant. The present study examined whether the recently introduced gender-neutral forms of nominalized adjectives and participles in German provide references that induce more balanced representations. We used cross-linguistic differences as a means to illustrate the flexibility of the gender representation system and investigated both native and nonnative (French–German bilinguals) speakers of German. Although a masculine bias persisted when participants read role nouns in the masculine plural form, the study suggests that the usage of nominalized forms can attenuate this male bias, even for nonnative speakers. The results of the study provide further support for the use of gender-neutral language.